Type 3 Secretion System (T3SS) of Bradyrhizobium sp. DOA9 and Its Roles in Legume Symbiosis and Rice Endophytic Association - Songwattana, Pongpan; Noisangiam, Rujirek; Teamtisong, Kamonluck; Prakamhang, Janpen; Teulet, Albin; Tittabutr, Panlada; Piromyou, Pongdet; Boonkerd, Nantakorn; Giraud, Eric; Teaumroong, Neung (Frontiers in Microbiology, 2017)
The Bradyrhizobium sp. DOA9 strain isolated from a paddy field has the ability to nodulate a wide spectrum of legumes. Unlike other bradyrhizobia, this strain has a symbiotic plasmid harboring nod, nif and T3SS genes. This T3SS cluster contains all the genes necessary for the formation of the secretory apparatus and the transcriptional activator (TtsI), which is preceded by a nod-box motif. An in silico search predicted 14 effectors putatively translocated by this T3SS machinery. In this study, we explored the role of the T3SS in the symbiotic performance of DOA9 by evaluating the ability of a T3SS mutant (ΩrhcN) to nodulate legumes belonging to Dalbergioid, Millettioid and Genistoid tribes. Among the nine species tested, four (Arachis hypogea, Vigna radiata, Crotalaria juncea, Macroptilium atropurpureum) responded positively to the rhcN mutation (ranging from suppression of plant defense reactions, an increase in the number of nodules and a dramatic improvement in nodule development and infection), one (Stylosanthes hamata) responded negatively (fewer nodules and less nitrogen fixation) and four species (Aeschynomene americana, Aeschynomene afraspera, Indigofera tinctoria and Desmodium tortuosum) displayed no phenotype. We also tested the role of the T3SS in the ability of the DOA9 strain to endophytically colonize rice roots, but detected no effect of the T3SS mutation, in contrast to what was previously reported in the Bradyrhizobium SUTN9-2 strain. Taken together, these data indicate that DOA9 contains a functional T3SS that interferes with the ability of the strain to interact symbiotically with legumes but not with rice.